Implementation of the Halal Product Guarantee Law in Indonesia by the Department of Industry and Trade Cooperatives of Bima City - Hakim, Lukmanul; Putri, Aisyah Karnila Nady (Nurani, 2022)
The obligation to register a halal certificate is stated in Article 4 of The Halal Product Guarantee Laws "Products that enter, circulate, and are traded in the territory of Indonesia must be certified halal". Therefore, the purpose of this study is to explain the mandatory implementation of halal certification carried out by the Department of Cooperative Industry and Trade of the Bima City for its Small & Medium-Sized Enterprises (SMEs), because it is one of the government instruments authorized to accommodate those who wish to register a halal certificate. The research method used in this research is descriptive qualitative, to support this research it takes several parties as respondents from the Department of Industrial and Trade Cooperatives and SMEs (DISKOPERINDAG) and so that this research can produce data that can provide conclusions regarding the implementation of mandatory halal certification by the Department of Cooperative Industry and Trade of the Bima City for its SMEs. From this research, it can be concluded that DISKOPERINDAG has carried out socialization in the form of seminars and training and provided information through the official website of DISKOPERINDAG Bima City. In addition to socialization, DISKOPERINDAG also provides assistance in procuring halal certificates for UMKM in the Bima City, it makes SMEs feel helped in registering halal certificates